Optimizing Early Childhood Education Management: Designing SISPAUD KB Ananda using End User Development (EUD) Method - Suryadilaga, Salli Risqi Warida; Raras AW, Chyntia; Pritama, Argiyan Dwi; Islamindiya, Syifa Fauziyah Nurul (JINAV: Journal of Information and Visualization, 2024)
Early childhood education at PAUD KB Ananda aims to develop knowledge and skills. To support this goal, PAUD KB Ananda has an online information system, "SISPAUD KB Ananda." This research uses the End User Development (EUD) method to involve end users in system development. The focus of the research includes facilitating the admission of new learners, dissemination of school information, and promotion through the system. Testing involved black box testing and user acceptance testing (UAT), with the results achieving a 100% success rate. SISPAUD KB Ananda succeeded in improving the process of admitting new students and expanding the dissemination of school information. Users recognized it as an effective administrative tool and promotional medium that facilitates schools. The system consists of a web profile of KB Ananda PAUD and an admission system, providing an efficient technical solution and a positive contribution to school operations and overall promotion.